MOTIVASI SISWA DALAM MENGERJAKAN PEKERJAAN RUMAH PADA MATA PELAJARAN IPA DI SDN 194/II SUNGAI PINANG KABUPATEN BUNGO - Aswana (Mat-Edukasia, 2019)
Science lessons require high creativity and motivation from students, so that motivation exists so that teachers need to assess the homework of students. This study aims to determine the Motivation of Students in Working on Homework at Science Subjects. This research is an experimental research. The study was conducted in two sample classes, each class numbering 24 students SDN 194/II Sungai Pinang and given different treatments. The research data was obtained from the final questionnaire. The results of the final questionnaire were analyzed using normal tests, homogeneity tests and Independent Sample T-tests. The results of the study showed the Sig (2-tailed) value of 0,000 < 0,05, so Ho was rejected and Ha was accepted. Based on the results of the study it was concluded that there were differences in motivation between group A learning motivation and group B learning motivation. Keywords: Motivation, Homework, Assessment